Takjil on The Road: Bersama Berbagi, Bersama Mengabdi - Eka Megawati; Meita Rezki Rezki Vegatama; Junety Monde; I Ketut Warsa; Debora Ariyani; Amirul Mukminin; Yuniarti Yuniarti (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity is motivated by the importance of fostering social awareness and a spirit of sharing with the community, especially during the month of Ramadan. The Takjil on the Road: Sharing Together, Serving Together program aims to provide direct benefits to the community, especially road users who are still active before breaking the fast, while also increasing the social awareness of students. The method used in this activity is a participatory approach that actively involves lecturers and students in every stage of the activity, from planning, preparation, implementation, to evaluation. The activity was carried out by distributing takjil packages to the community at predetermined locations. The results of the activity showed a positive response from the community and increased participation and social awareness of students in social activities. This activity is a tangible form of higher education's contribution to the community and a means of social learning for students.